2003
DOI: 10.1097/00004770-200310000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Mineral Trioxide Aggregate Using Two Different Techniques

Abstract: The purpose of this study was to determine if the adaptation of mineral trioxide aggregate (MTA) would differ when placed into simulated root canals of varying length when using two different placement and condensation methods. Hand condensation was compared to ultrasonic condensation. Eighty polyethylene tubes were divided into four groups of 20 tubes each. The tubes in the four groups were prepared to receive 3-, 5-, 7-, and 10-mm lengths of MTA respectively. Each group of 20 tubes was subdivided; 10 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
4
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 13 publications
2
110
4
4
Order By: Relevance
“…Hachmeister et al also found that the sealing ability of MTA is superior when used as an orthograde apical plug (4). Aminoshariae et al reported that hand condensation resulted in better adaptation and fewer voids than the ultrasonic method (11). In the present case, the MTA mixture was applied with a small plugger to the wall of the root-canal system to prevent extrusion of the material and the final adjustment was done with light force using the back end of sterilized paper points with the aid of the radiograph.…”
Section: Discussionmentioning
confidence: 87%
“…Hachmeister et al also found that the sealing ability of MTA is superior when used as an orthograde apical plug (4). Aminoshariae et al reported that hand condensation resulted in better adaptation and fewer voids than the ultrasonic method (11). In the present case, the MTA mixture was applied with a small plugger to the wall of the root-canal system to prevent extrusion of the material and the final adjustment was done with light force using the back end of sterilized paper points with the aid of the radiograph.…”
Section: Discussionmentioning
confidence: 87%
“…Valois et al (2004) 26 concluded for a better sealing ability, 4 mm thickness of MTA is required. Aminoshariae et al (2003) 27 showed that hand condensation was better than ultrasonic method as the MTA has a better adaptation to the walls with less voids in it.…”
Section: Comparative Properties Of Mta and Biodentine Mechanism Of Acmentioning
confidence: 99%
“…as bases under other re--storative dental materials). Some have pro--posed the use of Portland cement as an in--expensive alternative to other more expen--sive dental restorative materials for restora--tion of coronal defects [13], with potential uses in economically challenged areas. When used in such critical locations, both MTA and Portland cement must withstand compressive forces that could challenge their clinical longevity through time.…”
Section: Introduc!onmentioning
confidence: 99%